Unlocking the potential of exosomes: a breakthrough in the theranosis of degenerative orthopaedic diseases - Yue, Yaohang; Dai, Wei; Wei, Yihao; Cao, Siyang; Liao, Shuai; Li, Aikang; Liu, Peng; Lin, Jianjing; Zeng, Hui (Frontiers in Bioengineering and Biotechnology, 2024)
Degenerative orthopaedic diseases pose a notable worldwide public health issue attributable to the global aging population. Conventional medical approaches, encompassing physical therapy, pharmaceutical interventions, and surgical methods, face obstacles in halting or reversing the degenerative process. In recent times, exosome-based therapy has gained widespread acceptance and popularity as an effective treatment for degenerative orthopaedic diseases. This therapeutic approach holds the potential for “cell-free” tissue regeneration. Exosomes, membranous vesicles resulting from the fusion of intracellular multivesicles with the cell membrane, are released into the extracellular matrix. Addressing challenges such as the rapid elimination of natural exosomes in vivo and the limitation of drug concentration can be effectively achieved through various strategies, including engineering modification, gene overexpression modification, and biomaterial binding. This review provides a concise overview of the source, classification, and preparation methods of exosomes, followed by an in-depth analysis of their functions and potential applications. Furthermore, the review explores various strategies for utilizing exosomes in the treatment of degenerative orthopaedic diseases, encompassing engineering modification, gene overexpression, and biomaterial binding. The primary objective is to provide a fresh viewpoint on the utilization of exosomes in addressing bone degenerative conditions and to support the practical application of exosomes in the theranosis of degenerative orthopaedic diseases.